Becoming an Expert by Experience: Benefits and Challenges of Educating Mental Health Nursing Students. (2nd December 2021) - Happell, Brenda; Warner, Terri; Waks, Shifra; O'Donovan, Aine; Manning, Fionnuala; Doody, Rory; Greaney, Sonya; Goodwin, John; Hals, Elisabeth; Griffin, Martha; Scholz, Brett; Granerud, Arild; et al.
Abstract: Expert by Experience involvement in mental health nursing education is increasing in popularity as a teaching technique. The emerging literature attests to its benefits in enriching the educational experience for students. Much less attention has been devoted to the experience from the perspective of the Experts themselves. To address this gap and ensure this important perspective is captured and considered, the aim of this paper is to present the perceptions and experiences of Experts by Experience in delivering an educational module to mental health nursing students. A qualitative exploratory approach was adopted, involving in-depth individual interviews with Experts by Experience who delivered a learning module to nursing students in Australia and Europe. Data were analysed thematically. Analysis produced two overarching themes: Empowerment, and Challenges. Challenges included six sub-themes: Being constructive, not just critical; Time to unpack and reflect; Need for co-production and support from nursing academics; Emotional and practical support; maintaining personal boundaries; and adapting to the audience. These findings make a significant contribution to a broader understanding of Expert by Experience involvement in mental health education. The use of standards to maintain integrity and avoid tokenism is recommended.